An analysis of the normative parameters of reward and risk in Islamic finance - Mohamed Benaicha (ISRA International Journal of Islamic Finance, 2020)
Purpose: This study aims to define the parameters of the reward-risk principle in Islamic finance as established in the literature and discuss propositions that are presented on how such a principle is to be applied to Islamic banking products. Design/methodology/approach A descriptive approach is used to explore the normative parameters and criticisms of the application of reward-risk in Islamic finance. Findings The study finds that the principle of reward-risk is embodied in the multi-component concept of ʿiwaḍ (counter value) which must be evident in market transactions that involve commercial exchanges. The components include risk, costs, effort, value-adding and capital, all of which apply uniquely to different contractual forms of financing. Research limitations/implications The study uses academic literature and industry documents along with modest contact with prominent practitioners who provided general feedback on prevalent Islamic finance industry practices. Practical implications This study exposits the variety of approaches in applying the reward-risk principle and sheds light on the primary elements of the principle which will facilitate its greater consideration by the Islamic finance industry. Originality/value This study is a meaningful attempt at conveniently summing up and applying the parameters that are considered when discussing the scope of the reward-risk principle in Islamic finance.
Keywords: 330; AITAB; Islamic banking products; MMP; MPO; Reward-risk parameters